Blunted Cortisol Response Across Early Psychosis: Implications for Stress-Vulnerability Models and Clinical Staging. (September 2021) - Shah, Jai; McIlwaine, Sarah; Malla, Ashok; Joober, Ridha; Pruessner, Marita
Abstract : BG: Early psychosis is associated with elevated levels of subjective stress and abnormalities in hypothalamic-pituitary-adrenal axis functioning, including the blunting of cortisol stress response. However, it remains unknown whether this blunting is progressive or consistent across both clinical high-risk (CHR) and first episode psychosis (FEP) stages. In the context of clinical staging models, we examined cortisol response to the Trier Social Stress Test (TSST) between phases of early psychosis. Methods: We measured perceived stress and salivary cortisol before, during and after the TSST in individuals at CHR (n=28, mean age 19.1) and/or experiencing a FEP (n=60, mean age 22.9) compared with community controls (n=44, mean age 23.0). Results: Compared with controls, perceived stress is higher (p<0.05) and salivary cortisol is blunted (p< 0.01) in the combined early psychosis (CHR+FEP) sample across the entire TSST measurement period, not only following the speaking task. There were no differences in perceived stress or cortisol between the CHR and FEP groups. Conclusion: Despite evidence of elevated levels of diurnal cortisol, cortisol response to acute stressors may nonetheless be blunted throughout early psychosis. With high perceived stress, the observed blunting may be the culmination of ongoing stress sensitization pre-psychosis – with implications for theories of stress vulnerability, and for biomarkers and clinical staging in emerging mental illness.